Technology Creates 21St Century Wealth — Processes, Problems, and Prognosis - Zehner William Bradley; Williams Craig; Pletcher Gary (Marketing of Scientific and Research Organizations, 2017)
Science and technology are the driving forces increasing the global standards of living. The technology - wealth relationship is complex and not well understood presently but recent macro data tends to support Robert Solow’s 1957 observation that societal, company, and individual wealth and increased standards of living is created by application of science and technology to socio-economic challenges. In 1987, Robert Solow received the Nobel Prize in Economics, for his insight that “seven-eighths” of the world’s increase in world wealth is due to advances in science and technology. The challenges and costs of of wealth creation are identified. This paper explores wealth as defined by GDP/capita, and the current correlations between world/GDP per capita and R&D spending, the number of scientific and technical articles, and number of patents applications from 2000 to 2012/2013 with a forecast of world GDP/capita to 2025 of approximately $15,000 USD from today’s $10,000 USD.